Dyslipidemia among patients with type 2 diabetes mellitus visiting Specialized Center for Diabetes and Endocrinology - Fadhil, Badri; Abdul Jabbar, Mohammed (AL-Kindy College Medical Journal, 2014)
Background:The most common pattern of dyslipidemia in diabetic patients is increased triglyceride (TG) and decreased HDL cholesterol level, The concentration of LDL cholesterol in diabetic patients is usually not significantly different from non diabetic individuals, Diabetic patients may have elevated levels of non-HDL cholesterol [ LDL+VLDL]. However type 2 diabetic patients typically have apreponderance of smaller ,denser LDL particles which possibly increases atherogenicity even if the absolute concentration of LDL cholesterol is not significantly increased. The Third Adult Treatment Panel of the National Cholesterol Education Program (NCEP III) and the American Heart Association (AHA ) have designate diabetes as a coronary heart disease (CHD) equivalent and recommended treatment of LDL-c to < 2.6 mmoll (<100 mgldl)Objectives: We assessed the treatment ,type and control of dyslipidemia among adults with diabetes mellitus.Methods:This is a prospective study conducted in the Neurosurgical Hospital in Baghdad, Iraq, during the period from January 1999 to January 2001. Any patient admitted during the period of the study with clinical history, signs, symptoms, and contrast enhanced MRI suggesting a cerebral glioma and confirmed by postoperative histopathological results of glioma has been included in this study. While multifocal lesions, long-lasting epilepsy, use of antiepileptic therapy, multiple cranial lesions, previous cranial surgery, any chronic illness, and histopathological result of other tumors were exclusion criteria. All patients were at their first operation for brain tumors. Patients were examined by analyzing several functional domains (intelligence, executive functions, memory, language, praxis, gnosis and mood state) in order to establish the effect of tumor and surgery on cognition.Results:29 patients who fulfilled the selection criteria were included. Mean duration of clinical history was 5 months (range 1–9 months). At baseline, using test- and domain-based criteria, 79% and 38% of patients, respectively, were impaired, the former related to tumor factors such as edema (P <0.05), larger size (P <0.05) and higher grade (P = 0.001). Verbal memory, visuospatial memory and word fluency were the most frequently affected functions, partly associated with depression. Postoperatively, 38% and 55% of patients, respectively, were unchanged, 24% and 21% improved, and 38% and 24% worsened; 24% and 62% of patients were intact, respec¬tively.Conclusions:The extent of removal did not influence the outcome. Improvement involved previously impaired functions and was correlated with high-grade tumors. Worsening regar-ded executive functions was related to tumor size and was partly explained by radiological findings on postoperative MRI. This prospective study, focusing on the effects of tumor and surgery, showed that tumor significantly affects cognitive func¬tions, mainly due to the mass effect and higher grading. Surgical treatment improved the functions most frequently affected preoperatively and caused worsening of execu¬tive functions soon after operation, leaving the overall cognitive burden unchanged and capable of improvement prospectively